Comparison of crisis response planning and treatment as usual for active duty service members at risk for suicide: Study protocol for a stepped-wedge cluster randomized trial in a military treatment facility - Kristen H. Walter; Pia R. Khandekar; Alexander C. Kline; Erin L. Miggantz; Nicholas P. Otis; Lisa H. Glassman; Cynthia J. Thomsen; Guy Brock; Craig J. Bryan (Contemporary Clinical Trials Communications)
Background: Suicide is one of the leading causes of death among U.S. service members, and rates of suicide among military personnel have increased over the past two decades. To address this serious issue, effective preventive treatments are needed in settings where at-risk service members are frequently seen, such as emergency departments and inpatient psychiatric units. This study will compare the longitudinal effects of crisis response planning (CRP) and treatment as usual (TAU) on suicidal thoughts and behaviors among active duty service members seeking emergent care for suicidality at a military treatment facility. Methods: The current study is conducted through a consortium, Augmenting Suicide Prevention Interventions for Service Members. This article details an ongoing stepped-wedge cluster randomized clinical trial that compares rates of suicidal thoughts and behaviors among service members at risk for suicide following care from CRP-trained providers versus untrained providers (i.e., TAU). Participants complete assessments at pretreatment and every 3 months up to 1 year. Primary outcomes include suicide attempts and behaviors, and suicidal ideation is a secondary outcome. Moderators of treatment effects will also be examined. The methodological development of this trial is discussed, along with clinical and ethical considerations for suicide prevention research in emergency, inpatient, and military treatment settings. Conclusion: Providing evidence-based treatment for suicidality that addresses service members’ unique needs is crucial to reduce suicide rates and facilitate mental health recovery in this population. This study aims to inform future implementation and dissemination of CRP in healthcare systems to ultimately decrease suicide among service members. Clinical trials identifier: NCT05795764.